Are earnings quality attributes reflected in financial strength ratings?. Issue 3 (30th September 2014) - Ames, Daniel; S. Hines, Chris; Sankara, Jomo
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine whether earnings quality attributes are reflected in AM best's financial strength ratings (FSRs), a measure widely used in the insurance industry to assess financial health. Design/methodology/approach – Using a sample of insurance companies during the period 2006-2012, the authors measure the quality of reported earnings using three accounting-based measures: earnings persistence, accrual quality, and earnings smoothness. Findings – The authors find that better earnings persistence, higher accrual quality, and less earnings smoothing are reflected in higher FSRs for both public and private insurers, with the magnitude of the effect greater for private insurers. Originality/value – This is the first study of which the authors are aware that seeks to understand the impact, if any, of variations in the quality of reported financial information on the perceived financial health of firms by ratings agencies in the insurance industry. The authors also include a novel research design in assessing the determinants of financial health ratings. Users of FSRs should be aware of the impact of ownership structure on ratings agencies' propensity to incorporate reported earnings attributes in their ratings.